Assessment of the efficacy of 400 IU of oral Vitamin D3 supplementation for term healthy breastfed Indian infants - Kaifi Siddiqui,; Anwar Hasan Siddiqui,; Sheeba Farooqui,; Pradeep Kumar Ranbijuli, (Indian Journal of Child Health, 2021)
Introduction: Vitamin D is essential for growing children and its deficiency may have a catastrophic effect on growing children. Various reports state that Vitamin D deficiency is widely prevalent in the Indian population including infants and children. Objective: The objective of the study was to assess the efficacy of 400 IU of oral Vitamin D3 supplementation for term healthy breastfed Indian infants. Materials and Methods: The prospective, double-blinded cross-sectional study included 100 newborns divided into two randomized groups, A and B through a computer-generated program. Group A received 1 ml (400IU) Vitamin D drops daily for 3 months along with the breast milk whereas the Group B was only breastfed. Serum Vitamin D, Calcium, and alkaline phosphatase levels were measured in both the groups at birth and 3 months follow-up. Results: At birth no significant difference was observed in the serum level of Vitamin D, calcium and alkaline phosphatase in both the groups; however, at 3 month follow-up visit the Group A babies who were supplemented with Vitamin D 400 IU/day had a significantly more Vitamin D level (27.61 ± 11.95 ng/ml) compared with the babies of the non-supplemented group (10.56 ± 7.34 ng/ml). In the supplemented group, 46.7% had normal Vitamin D levels (>30 ng/ml), 20% had insufficiency (20–30 ng/ml) and 33.3% were deficient (30 ng/ml), 13.3% had insufficiency (20–30 ng/ml), and 86.7% were deficient (